Al-KalimÃ¢t al-’Arabiyah al-DakhÃ®lah fÃ® al-Lughah al-IndÃ»nÃ®siyah Lafdzhan wa Ma’nan wa AtsaruhÃ¢ fÃ® Ta’lÃ®m al-Lughah al-’Arabiyah - Umam, Muh Hotibul (Alibbaa’: Jurnal Pendidikan Bahasa Arab, 2020)
This study discusses Arabic words which are absorbed into Indonesian. The research background of this study is that teachers feel difficult to choose the right content to achieve appropriate goals for foreign beginners, prepare good educational materials for them, determine what should be first started from the lesson materials and show the discussions that require deep concentration. The method used to realize this research was a literature study by using documents such as Arabic and Indonesian books. It was analyzed using deductive and inductive analysis accurately until becoming independent analysis. The result showed that Arabic words which are absorbed into Indonesian in pronouncing and it’s meaning are Arabic words that are entered in Indonesian without changing the pronunciation (lafadz) and it’s meaning. There are two hundred and fifteen words that have been presented in this research, and most of them come from jamid or Mushtaq names. It has effects generally which include words absorption and others and it also has an effect specifically toward words absorption only.